Penyediaan Sumur Bor Dangkal sebagai Solusi Krisis Air pada Masyarakat Penyintas Bencana Banjir Gampong Keurumbok Kecamatan Kuta Blang Kabupaten Bireun - Cut Zukhrina Oktaviani; Alfa Taras Bulba; Halida Yunita; Fitrika Mita Suryani; Cut Mutiawati; Nafisah Al-Huda; Devi Sundary; Nurisra; Said Amir Azan (Universitas Syiah Kuala, 2026)
This community service program was conducted to address the clean water crisis experienced by flood-affected residents in Gampong Keurumbok, Kecamatan Kuta Blang, Kabupaten Bireuen. The flood disaster damaged and contaminated local water sources, disrupting the community’s access to safe water for daily needs. The program aimed to provide a reliable and sustainable clean water supply through the construction of a shallow tube well and to enhance community capacity in managing and maintaining water facilities. The target beneficiaries were households affected by the flood and facing limited access to clean water. A participatory approach was employed, including needs assessment, site survey, technical planning, tube well construction, and community assistance. The implementation strategy involved coordination with village authorities, site selection based on local hydrogeological conditions, and active community participation throughout the construction and maintenance processes. The results indicate that the shallow tube well successfully improved access to clean water, reduced dependence on contaminated water sources, and supported post-disaster recovery efforts. Furthermore, community involvement in the management of the facility contributed to the sustainability and long-term utilization of the clean water supply system.